DEVELOPING VIDEO AS THE TEACHING MEDIA OF WRITING DESCRIPTIVE TEXT FOR GRADE VIII STUDENTS IN SMP BRIGJEND. KATAMSO 1 MEDAN - Meyke Pratiwi Br. Karo; Sumarsih Sumarsih; Yeni Erlita (TRANSFORM : Journal of English Language Teaching and Learning, 2019)
This research was aimed to develop video as the teaching media of writing descriptive text for grade VIII students in SMP Brigjend.Katamso I Medan. This study was categorized as Research and Development (R & D) study which adapted from Borg and Gall (2003). The method through six phases: conducting need analysis, designing, developing, experts validating, revising, and final product. The subjects of this research were 40 students of grade eighth of SMP Brigjend. Katamso I Medan which was located in Jl. Sunggal No. 370 Medan. The data and data resources were the teacher’s lesson plan, teacher’s interview, and students’ questionnaires result. After getting the last data, the media should be planned to be designed as the students’ needs. The media were developed and had been validated by the experts. The percentages of the media from the experts were 90% that categorized as very good. It can be concluded that video as one of the creative media to improve the students’ ability in writing descriptive texts.Key words: Research and development (R&D),Descriptive Text, Video, Writing, Junior High School.